Chalcopyrite-pyrite mineralization associated with Precambrian trondhjemite-metagabbro intrusions, in the Skallevikhalsen of Lutzow-Holm Bay, Eastern Antarctica - Davaa-Ochir, Dashbaatar; Yoichi, Motoyoshi; Tomokazu, Hokada; Sotaro, Baba; Atsushi, Kamei; Ippei, Kitano; Prayath, Nantasin; Nugroho, Setiawan (2017)
第8回極域科学シンポジウム/個別セッション：[OG] 極域地圏 12月6日（水）国立極地研究所 3階セミナー室 The Eighth Symposium on Polar Science/Ordinary sessions: [OG] Polar Geosciences Wed. 6 Dec./3F Seminar room, National Institute of Polar Research conference object